Handbook of food processing equipment - Saravacos, George; Kostaropoulos, Athanasios E. (Switzerland Springer, 2016)
Contents: design of food processes and food processing plants; design and selection of food processing equipment; mechanical transport and storage equipment; mechanical processing equipment; mechanical separation equipment; heat transfer equipment;...
Includes bibliography and index
Keywords: Công nghệ thực phẩm